Artistic-Style Features of Marat Kabirov’s Intellectual Prose - Khakimovich, Ibragimov Bulat; Sagitovna, Sayfulina Flera; Kalibayevna, Abdyrasylova Gulmira; Maratovna, Talipova Gulfiya; Charisovna, Faizova Liliya (Journal of History Culture and Art Research, 2017)
This research, from an identification position in it art and style features, analyzes prosaic works of Marat Kabirov ("The mystery of yellow houses", "Goes the ghost", "A name of your angel") who represents the intellectual direction in modern Tatar literature. The subject of studying of scientific work is made by esthetic specifics of this direction of the Tatar prose, art and style features of works, representative from the point of view of the characteristic of intellectualization in national historic-literary process as qualitatively new literary phenomenon in the Tatar prose of the end of 20 - the beginnings of the 21 century. Modern literary critics mark out the most general property of all intellectual texts as belonging to modernist and postmodern literary tradition", inter-text, literary and historical hints, metaphoricalness, etc. In the analyzed M. Kabirov’s works not separate images, not separate lines become metaphors, but the work in general is a difficult, polysynthetic, multiple-valued metaphor, a metaphor symbol. In these works readers gradually become as if accomplices of the event, "move" in the text of a plot as equals with the author and heroes, that there is a dialogue mode of reading of the work as one of indicators of intellectualization of prose.